Antimicrobial Susceptibility Testing of 59 Strains of Campylobacter fetus subsp. fetus - Tremblay, Carole (American Society for Microbiology, 1998)
The susceptibilities of 59 Campylobacter fetus subsp. fetus isolates to eight antibiotics were studied by the agar dilution, E-test, and disk diffusion methods. None of the isolates were β-lactamase producers. All were susceptible to ampicillin, gentamicin, imipenem, and meropenem as determined by the three methods, with MICs at which 90% of the isolates are inhibited (MIC(90)s) (determined by agar dilution) of 2, 1, ≤0.06, and 0.12 μg/ml, respectively. Twenty-seven percent of the isolates were resistant to tetracycline, with complete agreement between the agar dilution and disk diffusion results. The MIC(90)s determined by agar dilution were 2 μg/ml for erythromycin, 1 μg/ml for ciprofloxacin, and 8 μg/ml for cefotaxime.